The effect of ageing on presentation, management and outcomes in degenerative cervical myelopathy: a systematic review. (19th November 2020) - Grodzinski, Ben; Durham, Rory; Mowforth, Oliver; Stubbs, Daniel; Kotter, Mark R N; Davies, Benjamin M
Abstract: Objective: Degenerative cervical myelopathy (DCM) is a disabling neurological condition. The underlying degenerative changes are known to be more common with age, but the impact of age on clinical aspects of DCM has never been synthesised. The objective of this study is to determine whether age is a significant predictor in three domains—clinical presentation, surgical management and post-operative outcomes of DCM. Methods: a systematic review of the Medline and Embase databases (inception to 12 December 2019), registered with PROSPERO (CRD42019162077) and reported in accordance with preferred reporting items of systematic reviews and meta-analysis (PRISMA) guidelines, was conducted. The inclusion criteria were full text articles in English, evaluating the impact of age on clinical aspects of DCM. Results: the initial search yielded 2, 420 citations, of which 206 articles were eventually included. Age was found to be a significant predictor in a variety of measures. Within the presentation domain, older patients have a worse pre-operative functional status. Within the management domain, older patients are more likely to undergo posterior surgery, with more levels decompressed. Within the outcomes domain, older patients have a worse post-operative functional status, but a similar amount of improvement in functional status. Because of heterogenous data reporting, meta-analysis was not possible. Conclusion: the current evidence demonstrates that age significantly influences the presentation, management and outcomes of DCM. Although older patients have worse health at all individual timepoints, they experience the same absolute benefit from surgery as younger patients. This finding is of particular relevance when considering the eligibility of older patients for surgery.